FAKTOR-FAKTOR PENDUKUNG DAN PENGHAMBAT EFEKTIVITAS STUDENT CENTERED LEARNING (SCL) MAHASISWA KEDOKTERAN - Resti Rahmadika Akbar; Mifa Kalbu Anggraini; Halifah, Nur (Nusantara Hasana Journal, 2025)
Student Centered Learning (SCL) is an innovation in learning methods whose aim is.to enhance students' comprehension of the subject matter and experience while teaching them to think critically, creatively, and logically.This method is applied by medical students by conducting student-focused learning. The aim of this study to determine the elements that promote and hinder medical students' ability to benefit from SCL. The approach is a survey of the literature by looking at a number of relevant factors supporting and inhibiting the effectiveness of student centered learning (SCL) for medical students. Based on search results via Google Scholar, PubMed, and EBSCO, 30 journals were idetified that were eligible. The systematic review's findings lead to the conclusion that there are many supporting and inhibiting factors for the effectiveness of SCL, but this method is considered to help students to collaborate and have broader thinking.